Rare presentation of rectal duplication cyst as perineal hernia in an adult. Issue 4 (13th April 2021) - Bhat, Rahul; Choudhari, Rajat Ravindrakumar; Prabhu, Shivananda; Thejeswi, Poornachandra
Abstract : Rectal duplication cysts are rare congenital anomalies of the gastrointestinal tract. They can present with pain, gastrointestinal bleeding, infection or compressive symptoms on the rectum and urinary bladder. A 79-year-old man presented with a 8×5 cm swelling in the sacral region above the natal cleft with a positive cough impulse. During surgical exploration, there were two cysts with the posterior one presenting as the hernia. The cyst was excised and histopathological examination confirmed a diagnosis of rectal duplication cyst. Rectal duplications can lie anterior or more commonly posterior to the rectum. Differential diagnoses include dermoid cyst, diverticular cyst, sacrococcygeal teratoma or meningocele and endoscopic ultrasound is imaging of choice for diagnosis. Surgical excision is the treatment of choice. This is a rare presentation of a rectal duplication cyst as a perineal hernia with only a handful of cases in literature.